1970
DOI: 10.3329/akmmcj.v2i2.8168
|View full text |Cite
|
Sign up to set email alerts
|

Friedewald’s Formula is Applicable up to Serum Triacylglycerol to Total Cholesterol Ratio of Two in Bangladeshi Population

Abstract: Friedewald's formula is the most frequently used formula for the calculation of serum lowdensity lipoprotein cholesterol from serum total cholesterol, serum triacylglycerol and serum high-density lipoprotein cholesterol. Most laboratories use serum triacylglycerol concentration of 400 mg/dl as upper cut-off limit for the calculation of LDL cholesterol, but a combination of serum triacylglycerol to total cholesterol ratio and serum triacylglycerol may have more advantages than serum triacylglycerol concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…1B). This observation is consistent with the findings of previous studies as reported elsewhere [14][15][16][17][18][19][30][31][32].…”
Section: Characteristics Of Equation Derivation and Equation Validatisupporting
confidence: 83%
See 1 more Smart Citation
“…1B). This observation is consistent with the findings of previous studies as reported elsewhere [14][15][16][17][18][19][30][31][32].…”
Section: Characteristics Of Equation Derivation and Equation Validatisupporting
confidence: 83%
“…In Bangladeshi population, underestimation of LDLC by FF has been reported [30][31][32] and there is no evidence of systematic over estimation of LDLC by FF in this population [30][31][32]. No study has yet been carried out for the modification or derivation of equation to calculate LDLC in Bangladeshi population.…”
Section: Introductionmentioning
confidence: 99%
“…But this formula underestimates LDL cholesterol in different populations studied as well as in Bangladesh. 3,4,5,6 A recent study in our population proposed a modification of Friedewald's formula to calculate LDL cholesterol up to serum TG concentration of 1000 mg/dL. 7 The modification of Friedewald's formula was based on the absolute differences between direct LDL cholesterol and LDL cholesterol calculated by Friedewald's formula (ÄLDL cholesterol) and the linear regression equation of the absolute difference with serum triglyceride to total cholesterol ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The cases were admitted ischaemic stroke patients diagnosed with computerized tomographic scan and confirmed by a neurologist whereas apparently normal subjects without any history of CVD attending the hospital for medical check-ups served as controls. Patients with chronic kidney disease (protein-creatinine-ratio greater than 0.3 in women and 0.2 in men and/or eGFR < 60 mL/min/1.73 m 2 ) [16], were exempted from the study.…”
Section: Study Population and Subject Recruitmentmentioning
confidence: 99%